2020
DOI: 10.1364/oe.384039
|View full text |Cite
|
Sign up to set email alerts
|

Solution-processed antireflective coating for back-contact perovskite solar cells

Abstract: Back-contact architectures for perovskite solar cells eliminate parasitic-absorption losses caused by the electrode and charge collection layers but increase surface reflection due to the high refractive index mismatch at the air/perovskite interface. To mitigate this, a ∼85 nm thick layer of poly(methyl methacrylate) (PMMA), with a refractive index between those of air and perovskite, has been applied as an antireflective coating. Transfer matrix modelling is used to determine the ideal PMMA layer thickness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…Deposition of protective coatings such as poly(methyl methacrylate) onto the perovskite can further enhance the device stability and efficiency. [28] Further optoelectronic measurements were conducted on these devices to gain an understanding of the underlying mechanism for the aforementioned observations. Following previous literature, TPV decay measurements were conducted to probe the charge recombination behavior.…”
Section: Photovoltaic Performance Of Devices Comprising Mesoporous Quasi-interdigitated Back-contact Electrodesmentioning
confidence: 99%
“…Deposition of protective coatings such as poly(methyl methacrylate) onto the perovskite can further enhance the device stability and efficiency. [28] Further optoelectronic measurements were conducted on these devices to gain an understanding of the underlying mechanism for the aforementioned observations. Following previous literature, TPV decay measurements were conducted to probe the charge recombination behavior.…”
Section: Photovoltaic Performance Of Devices Comprising Mesoporous Quasi-interdigitated Back-contact Electrodesmentioning
confidence: 99%
“…[204,205] The fast-growing micro-nano processing technology enables the successful design and construction of various nano-patterns in photovoltaic devices, including micron-level pyramids, inverse opal structures, diffraction gratings, antireflective coatings, and other geometric structures. [204,206] Such nano-patterns have been proved to enhance the photon absorption and increase the device photocurrent. In QDSCs, by designing a submicron periodic photonic structure on the bottom electrode, the photon localization, or optical waveguide effect helps to increase the propagation distance of photons in the absorption layer.…”
Section: Nanophotonic Structure Designmentioning
confidence: 99%
“…This includes perovskite solar cells which reached a record high efficiency of over 25% (Cheng et al, 2014;Xie et al, 2018;Corzo et al, 2020;Lim et al, 2021b). In addition, recent studies have demonstrated that the use of various protective and antireflective coatings, such as intrinsic a-Si:H layers, among others, can considerably enhance the performance of future generations of thin film solar cells (Uzum et al, 2017;Zhao et al, 2017;Li et al, 2020a;Bacal et al, 2020;Qu et al, 2021). The scientific community devoted to semitransparent solar cell technology research may consider the recent advent of monolithic Perovskite/Si tandem solar cells as a unique opportunity to reshape the current knowledge in the field, allowing the possibility to reach the Shockley-Queisser theoretical efficiency limit of 33% (Ail-Ashouri et al, 2020;Lu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%